2019
DOI: 10.3390/app9183759
|View full text |Cite
|
Sign up to set email alerts
|

Damping Assessment of Lightweight Timber Floors Under Human Walking Excitations

Abstract: Vibrations on timber floors are among the most common serviceability problems in social housing projects. The presence of low damping levels on these floors could cause excessive vibrations in a range of frequency and amplitude that generate discomfort in users. This study focuses on the influence of the damping ratio in the dynamic serviceability of social housing timber floors due to walking excitations. More than 60 human-walking vibration tests were conducted on both laboratory and in-situ timber floors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Previous research [ 32 ] has shown that Operational Modal Analysis (OMA) is useful for estimating the dynamic properties of structural timber elements from vibration response measurements only, both in laboratory and in-situ construction contexts. Over the years, several OMA methods have been developed, classified as parametric and non-parametric.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research [ 32 ] has shown that Operational Modal Analysis (OMA) is useful for estimating the dynamic properties of structural timber elements from vibration response measurements only, both in laboratory and in-situ construction contexts. Over the years, several OMA methods have been developed, classified as parametric and non-parametric.…”
Section: Methodsmentioning
confidence: 99%
“…In residential buildings, vibrations and the consequent noise caused by footsteps are the major source of human discomfort and often manifest as short-term transient oscillations. Hence, several studies have conducted vibration tests of floors by employing real footfalls as the excitation source [23,[25][26][27]. However, assuming that for small-amplitude vibrations the response is linear, the response of the floor to a footfall can be obtained by convolution of the temporal profile of a footfall with the impulse response of the floor.…”
Section: Impact Response Testsmentioning
confidence: 99%
“…Probability density functions were used to evaluate the vibration responses. Opazo-Vega et al [7] proposed a experimental method to estimate damping of lightweight timber floors. Damping is an important parameter to be identified accurately.…”
Section: Vibration Analysis Of the Complex Dynamic Systems By Numericmentioning
confidence: 99%